2007
DOI: 10.1097/01.mlg.0000246197.89602.cb
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Complication Rate in Percutaneous Dilation Tracheostomies

Abstract: PDT provides an easy and convenient alternative to open tracheotomy (OT) and should be added to the otolaryngologist's armamentarium of surgical airway procedures. The complication rate of PDT is low and similar to that of open operative tracheotomy. However, with experience and the use of strict protocols in both patient selection and PDT procedure, the complication rate can be significantly reduced further both in frequency and severity, making it even safer than an open operative tracheotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…Simultaneous video bronchoscopy was also used by a majority of physicians in this study; this also is similar amongst both disciplines. The use of simultaneous video bronchoscopy while performing PT has been shown to significantly reduce intraoperative complications such as false passage and tracheoesophageal puncture or bleeding and is a practice that is strongly recommended by experts and by many of the percutaneous tracheotomy manufacturers [8][9][10]17]. These data suggest that the procedure performed by the two specialties is currently comparable.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Simultaneous video bronchoscopy was also used by a majority of physicians in this study; this also is similar amongst both disciplines. The use of simultaneous video bronchoscopy while performing PT has been shown to significantly reduce intraoperative complications such as false passage and tracheoesophageal puncture or bleeding and is a practice that is strongly recommended by experts and by many of the percutaneous tracheotomy manufacturers [8][9][10]17]. These data suggest that the procedure performed by the two specialties is currently comparable.…”
Section: Discussionmentioning
confidence: 80%
“…A 2007 meta-analysis concluded that although PT may have more early complications than open tracheotomies, long-term complications between the two techniques appear similar [8,9]. More recent studies have examined ways to reduce morbidity from the procedure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…23,30,31 Some investigators have adequately addressed these challenges by use of blunt dissection and illumination by the FFB through the newly exposed, thinner section of tissue. 32,33 However, the presence of the FFB itself within the ETT is cause for concern 20,34 as the cross-sectional diameter of the ETT is effectively reduced by 41% to 76% (with a 5.7 mm OD FFB in a 9.0 mm and 7.0 mm ID ETT, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Severe acute complications including death were only reported in few cases. 25 Bhatti et al 26 showed a reduction of the acute complication rate during the years correlating with an increased familiarity of physicians with the procedure. Therefore, percutaneous dilatational tracheotomy has become a standard procedure in many ICUs.…”
Section: Discussionmentioning
confidence: 98%